Strengthening ministries of health for primary health care : report of a WHO Expert Committee, meeting held in Geneva from 10 to 16 November 1987 - WHO Expert Committee on Strengthening Ministries of Health for Primary Health Care; World Health Organization (Geneva : world Health Organization, 1988)
Reports the findings and recommendations of a group of experts concerned with the major causes of weaknesses in ministries of health and what must be done to strengthen them. Emphasis is placed on the better use of all resources, which is possible only when ministries of health are strong, well organized, well managed, and securely financed. The report opens with a clarification of the term ministry of health and an outline of the range of functions in any national health system. The second section enumerates reasons why ministries of health fail to serve as the directing and coordinating authorities for all health activities in the national health system. Reasons range from problems of management and leadership to the poor bargaining position of ministries of health when competing for a share in the national budget. The most extensive part of the report presents and discusses seven strategies for overcoming these widespread weaknesses.
1. Introduction -- 2. Ministries of health and health for all -- 3. Ministry of health weaknesses and their background -- 4. Strategies for strengthening ministries of health -- 5. Achieving changes -- 6. Principal conclusions and recommendations -- Acknowledgements -- References
Keywords: Primary Health Care; National Health Programs; Community Health and Primary Health Care